Case report: Cardiac intimal sarcoma in a young child - Verbeek, Sanne; Sciot, Raf; Debiec-Rychter, Maria; Labarque, Veerle; Meyns, Bart; Cools, Bjorn (Frontiers in Pediatrics, 2023)
Undifferentiated mesenchymal tumors from the intimal layer (intimal sarcomas) are rare within the ventricles and exceptional in children. A rare case of an intimal sarcoma located in the right ventricle in a young child is presented with need for urgent surgical resection due to mechanical flow obstruction. Tumor cells showed amplification of MDM2 gene and a homozygous loss of CDKN2A on 9p21. A review of the literature regarding primary cardiac malignancies and intimal sarcoma in children is provided.